Introducing 4-H Youth Development - Marilyn N. Norman; Joy C. Jordan (EDIS, 2006)
Youth development has been defined as an ongoing process through which young people attempt to meet their needs and to develop the competencies they perceive as necessary for survival and transition to adulthood. Positive Youth Development is development that is positive and productive for both youth and their communities. This document is 4-HS FS101.2, one of a series of the 4-H Youth Development Department, UF/IFAS Extension. Published May 2006.